Strong induction of 4-1BB, a growth and survival promoting costimulatory receptor, in HTLV-1-infected cultured and patients' T cells by the viral Tax oncoprotein - Pichler, Klemens; Kattan, Tarek; Gentzsch, Juliane; Kreß, Andrea; Taylor, Graham P.; Bangham, Charles R. M.; Grassmann, Ralph (Blood, 2008)
Human T-cell leukemia virus type 1 (HTLV1), the cause of adult T-cell leukemia, stimulates the growth of infected T cells in cultures and in nonleukemic patients. In the latter, HTLV-1 is found in long-term persisting T-cell clones. The persistence of normal T cells is controlled by the growth-stimulating and antiapoptotic functions of costimulatory receptors, while the growth-stimulating HTLV-1 functions are mediated by the viral oncoprotein Tax. Here we analyzed the impact of Tax on costimulatory receptors in T cells with repressible Tax and found that among these receptors 4-1BB (TNFRSF9/CD137/ILA) was induced most strongly. Upregulated 4-1BB expression was a consistent feature of all HTLV-1-infected cell lines, whether patient-derived or in vitro transformed. Tax was sufficient to induce the expression of the endogenous 4-1BB gene in uninfected T cells, and it strongly activated (45-fold) the 4-1BB promoter via a single NF-κB site. The ligand of 4-1BB was also found on transformed T-cell lines, opening up the possibility of autostimulation. Moreover, 4-1BB expression in patients' lymphocytes ex vivo correlated with Tax expression, strongly suggesting Tax-mediated 4-1BB activation in vivo. Thus, 4-1BB up-regulation by Tax could contribute to growth, survival, and clonal expansion of the infected cells during persistence and disease. © 2008 by The American Society of Hematology.
Created from Fastlane, Scopus look-up